Association of IL28B (IFNL3) rs12979860 mRNA levels, viral load, and liver function among HCV genotype 1a patients - Mousavi Nasab, Seyed Dawood (Gastroenterol Hepatol Bed Bench, 2019)
AIM: The present study was designed to evaluate the correlation of interleukin 28B (IL28B, IFNL3) rs12979860 mRNA levels, viral load, and liver function among hepatitis C virus (HCV) patients genotype 1a. BACKGROUND: HCV is considered essentially hepatotropic and is a major health problem around the world. METHODS: This study included 100 HCV-infected patients with HCV genotype1a (G1a) and rs12979860 CC genotype. These patients were divided into two groups according to HCV treatment. Aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), and HCV Load were measured and recorded for each patient. IL28B mRNA levels were determined using real-time polymerase chain reaction assay, and their correlation with clinical data were analyzed. STRING was applied to construct a network and identify interactions between IL28B (IFNL3) and its significant neighbor proteins. RESULTS: The results revealed a significant relationship between the ALT as well as ALP levels with IL28B rs12979860 mRNA expression level in men, and also with age >50 years. In the treated group, AST level and HCV load had a significant relationship with IL28B mRNA expression level. The results showed that the level of ALP and AST decreased significantly with increased IL28B mRNA expression level in the treated and untreated group, respectively. STRING database showed that IL28B (IFNL3) interacted with ten important neighbor proteins with some of these proteins being involved in signal transduction pathway activating antiviral response. CONCLUSION: This study indicated that rs12979860CC genotype could predict IL28B mRNA expression level in HCV-infected patients with G1a. Furthermore, IL28B mRNA expression level may serve as a useful marker for the development of G1a HCV-associated outcomes.